COMPARISON OF THE THICKNESS OF RICE STRAW MULCH, RICE HUSK AND REEDS ON THE OBSERVATION OF THE NUMBER OF FRUIT PLANTS TOMATO (Solanum lycopersicum) - Sunaryo; Shella Ramadhanty, Erlinda; Kristianto, Sonny (Journal of Natural Sciences and Learning, 2023)
Mulch is a surface covering material used to prevent weed growth, protect soil moisture, keep the soil structure stable and protect against erosion. The thickness of the mulch itself is also very influential on the life processes and development of plants. This study aims to determine and study the ratio of types of mulch thickness to observations of the number of fruits of tomato plants.method was used literature review by searching several journals that discussed the thickness of mulch of various types of organic mulch, namely rice straw, rice husk, and reeds using the search engine Google Scholar and Connected Papers with the keywords mulch thickness, type -types of organic mulch, and tomato plants. Several journals show that the difference in dosage or thickness of mulch which is consistent with one level higher than low content is significantly different which affects plant height, number of branches, number of flowering, and number of fruit produced. So it can be concluded that the use of organic mulch is very good for improving the quality of tomato plants and plays an important role in maintaining the stability of temperature, humidity and nutrients in the soil.